(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Clinacanthus nutans (C. nutans), or “Belalai gajah,” is traditionally used to treat microbial infections, cancer, inflammation, and diabetes due to its rich phytochemical profile. This study aimed to extract bioactive compounds from C. nutans leaves using varying methanolic concentrations (100%, 70%, and 60% v/v) and evaluate their total phenolic content (TPC), antioxidant, antimicrobial, and apoptotic activities. Extraction yields were 8.50%, 15.80%, and 14.70% for 100%, 70%, and 60% methanol extracts, respectively. The 100% methanol extract showed the highest TPC (23.40 mg GAE/g), followed by 70% (20.48 mg GAE/g) and 60% (20.32 mg GAE/g). Antioxidant activity assessed by DPPH assay showed the strongest radical scavenging in the 100% extract (IC₅₀ = 1.13 mg/mL), followed by 70% (1.87 mg/mL) and 60% (2.82 mg/mL). Only the 60% and 70% extracts exhibited antimicrobial activity with a minimum inhibitory concentration (MIC) of 10 mg/mL. Cytotoxicity assessed by MTT assay on CT26 cells revealed the lowest IC₅₀ for the 100% extract (0.18 ± 0.071 mg/mL), followed by 70% (0.20 ± 0.062 mg/mL) and 60% (0.49 ± 0.042 mg/mL). Apoptotic populations in CT26 cells, determined via Trypan Blue assay, were 47.34% ± 8.89, 44.37% ± 2.34, and 43.00% ± 0.95 for the 100%, 70%, and 60% extracts, respectively. These findings suggest that C. nutans exhibits promising antioxidant, antimicrobial, and anticancer properties, supporting its potential as a natural therapeutic agent. Further studies are needed to explore its mechanisms, dosage optimization, and synergistic interactions with other compounds.